A cross-sectional study on the role of hematological and inflammatory biomarkers as predictor of mortality at the time of admission among COVID-19 patients - Totade, Sanjay Kumar; Daheria, Chanchlesh; Morya, Rajesh Kumar; Bhagwan Singh Yadav,; Varma, Amit; Toppo, Neelam (Asian Journal of Medical Sciences, 2023)
Background: Whole world experienced COVID-19 pandemic with more than 155 million cases and >3.4 million deaths. Vasculitis and immune system activation plays a critical role in pathogenesis, especially in severely ill and non-survivors COVID-19 patients. Aims and Objectives: The aim of the study was to establish the role of hematological indices and inflammatory biomarker as predictors of mortality among non-survivor and survivor COVID-19 cases at the time of admission. Materials and Methods: The cross-sectional study was conducted at a dedicated COVID-19 referral hospital from July 2020 to August 2020, among 300 real time-polymerase chain reaction confirmed COVID-19 cases. Demographic, clinical, comorbidity, laboratory investigation, and outcome data were collected from patient’s medical record. Outcome variables – discharged (survived) or death (non-survived) were considered for comparison of various hematological indices and inflammatory biomarkers. Data are represented as median, IQR (Q1-Q3) and difference between median and proportions were calculated by Mann–Whitney U-test and χ² test. A predictive power of laboratory parameters between survivors and non-survivors was evaluated using receiver operant curve (ROC) analysis and area under the ROC curve (AUC). Results: The median age of non-survivors was significantly higher than survivors. Hypertension was significantly associated with non-survivors. Hematological parameters such as total leukocyte count, absolute neutrophil count, Neutrophil: Lymphocyte ratio were significantly increased with lymphocytopenia (P=0.001), and Inflammatory biomarkers such as C-reactive protein (CRP), lactate dehydrogenase, D-dimer, ferritin, procalcitonin, and NT-Pro BNP, all were significantly increased in non-survivors patients (P=0.001). CRP and neutrophil lymphocyte ratio (NLR) showed “Good” predictive value for mortality with cutoff value of 74.0 mg/l (AUC=0.841, Sensitivity=80.4%, Specificity=73.0%) and 5.65 (AUC=0.805, Sensitivity=76.1%, Specificity=73.0%), respectively. Pro-BNP showed “Fair” predictive value for mortality with cutoff value of 330.5 pg/ml (AUC=0.726, Sensitivity=73.9%, Specificity=58.2%). Conclusion: We suggest that CRP, NLR, and Pro-BNP can be used as a screening tool to predict mortality in COVID-19 patients for timely intervention to save valuable life, especially when sensitivity toward severity of COVID-19 among medical health professionals and general public is on decline.